2007
DOI: 10.1111/j.1467-9507.2007.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

The Centrality of Gender and Ethnic Identities across Individuals and Contexts

Abstract: This study examined (1) whether 5-to 12-year-old children consider gender and ethnicity to be central and important components of their identity, (2) whether the relative centrality of these identity components differs across children, and (3) how the centrality of children's gender and ethnic identities is affected by a dynamic situational context of inclusion and exclusion. Results indicate that although gender and ethnicity are not the most important aspects of elementary schoolchildren's self-concepts, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 47 publications
5
73
3
Order By: Relevance
“…This finding is important because prior work with ethnic-racial minority (i.e., Latino/a, African-American, Asian, and ethnic-racial majority (i.e., White) children indicated that children rated ethnicity-race as less central to their self-concept than other categories (e.g., after school activities; Turner & Brown, 2007); however, our findings suggest that ethnicity-race is central to girls with darker skin tones, a novel contribution of this study. Thus, future research focused on children’s ethnic-racial centrality should consider skin tone and gender.…”
Section: Discussionmentioning
confidence: 90%
“…This finding is important because prior work with ethnic-racial minority (i.e., Latino/a, African-American, Asian, and ethnic-racial majority (i.e., White) children indicated that children rated ethnicity-race as less central to their self-concept than other categories (e.g., after school activities; Turner & Brown, 2007); however, our findings suggest that ethnicity-race is central to girls with darker skin tones, a novel contribution of this study. Thus, future research focused on children’s ethnic-racial centrality should consider skin tone and gender.…”
Section: Discussionmentioning
confidence: 90%
“…Future work that attempts to draw conclusions about the effectiveness of single-sex schooling for racial/ethnic groups should consider the groups' numeric majority or minority status within both the school and the broader society. Another possible explanation is that the relative importance of gender identity may vary based on ethnicity (Corby, Hodges, & Perry, 2007;Turner & Brown, 2007). The African American girls in this sample may have placed less emphasis on gender than other students, and thus felt less of a connection to the other students at the school based on their shared gender.…”
Section: Discussionmentioning
confidence: 94%
“…Some quantitative research on the topic has involved comparisons within samples that can be subdivided according to two overlapping groups, such as ethnicity and gender, to allow comparisons among, say, Black males, white males, Black females, and white females. Other research has looked at similar aspects of two types of identity; for example, Turner and Brown (2007) examined the centrality of gender and ethnicity in children along with other aspects of the self-concept. To take the study of intersectionality further, studies are needed that assess similar aspects (such as strength of attachment, extent of exploration, or centrality) of two or more identities and then follow participants longitudinally and examine the ways in which these aspects are related to each other and influence the development of each other over time.…”
Section: Intersectionalitymentioning
confidence: 98%